Hello,
6 - (-3) = 9
-7 - 5 = -12
Answer:
b=34
Step-by-step explanation:
<a(340 corresponds to <b
−3xy(2x2 + 3xy − 4y2)
−3xy(2x2 − 3xy + 4y2)
−3(2x3y − 3x2y2 + 4xy3
Answer:
Option C is the answer.
Step-by-step explanation:
We have to factor the GCF of the given expression:
-6x³y + 9x²y² - 12xy³
To get the GCF of the given expression we will find the factors of each term first.
Factors of 6x³y = 2 × 3 × (x) × (x) (x) (y)
Factors of 9x²y² = 3 × 3 × (x) (x) (y) (y)
Factors of 12xy³ = 2 × 2 × 3 × (x) (y) (y) (y)
So the common factor is 3 × (x) (y)
Now we will take out the GCF as a factor of the given expression = 3xy (-2x² + 3xy - 4y² )
= -3xy ( 2x² - 3xy + 4y² )
Option C is the answer.
Answer:
228
Step-by-step explanation:
22*10-220
220+8=228
Hi there! :)
Answer:
y=50
*The answer must have a positive sign.*
Step-by-step explanation:
First, you switch sides.
Then, you subtract by 37 from both sides of an equation.
You subtract by the numbers from left to right.
Final answer is y=50
Hope this helps!
Thanks!
-Charlie
Have a nice day! :)
:D